Computed tomography and magnetic resonance imaging findings of nasal chondromesenchymal hamartoma in a young child: a case report. Issue 8 (August 2020) - Cui, Ya-qiong; Wang, Li-li; Huang, Gang; Zhao, Lian-ping
Nasal chondromesenchymal hamartoma (NCMH) is a rare destructive benign neoplasm that predominantly develops in infants and young children. The lesion is usually located in the nasal cavity, often in the adjacent paranasal sinuses and orbital region and especially in the ethmoid sinus. Because the imaging characteristics of NCMH often mimic the features of malignant tumors, it is clinically important to study the radiographic appearance of this disease. Therefore, we herein present the computed tomography and magnetic resonance imaging findings of NCMH occurring in a 7-year-old girl. The mass was resected via an endoscopic surgical approach and definitively diagnosed as NCMH based on histologic and immunohistochemical analysis. However, signs of tumor recurrence manifested 45 months after surgery. NCMH can be locally aggressive with an expansive and destructive radiographic appearance, which highly implies a malignant neoplasm. Hence, an accurate diagnosis is essential to avoid potentially harmful therapies, and detailed computed tomography or magnetic resonance imaging should be performed prior to surgery. Selective arterial embolization is also an important part of preoperative management because the degree of enhancement may not be adequate to determine the blood supply of the tumor. Moreover, complete radical excision cannot guarantee that the lesion will not recur.